Improving The Structure of Linguistic Texts in Phrases with A Project-Based Learning Model (PJBL) - Sirhamsyah Sirhamsyah; Romiati Ritonga; Filzah Hamzah (JP2D (Jurnal Penelitian Pendidikan Dasar) UNTAN, 2023)
This study aims to improve knowledge and understanding of the structure of the linguistic text in the phrases of each student. They do not know exactly which material will be given when starting the learning process. The material was conveyed using the stages from easy to challenging to improve the ability and knowledge through the PjBL method with a quantitative descriptive research approach. Classroom Action Research (CAR) is a way of determining how to do it with cycle I and II. The way to obtain the data is known as data collection methods. Data analysis with cycle I passed 22 students with a percentage of 78% and continued to cycle II with improvements in planning and implementation using new PjBL have passed 28 students with a percentage of 100%. The topic of a linguistic text structure in the phrases using the PjBL model can help students to understand the topic because there is effective management if they have several difficulties during the learning process.